Energy balance and partitioning over grasslands on the Mongolian Plateau. (February 2022) - Chen, Jingyan; Dong, Gang; Chen, Jiquan; Jiang, Shicheng; Qu, Luping; Legesse, Tsegaye Gemechu; Zhao, Fangyuan; Tong, Qi; Shao, Changliang; Han, Xingguo
Highlights: The dynamics of energy fluxes were very different among the four grasslands on Mongolian Plateau. Net radiation of the shrubland was 20% lower than that of meadow steppe. Bowen ratio of typical steppe and shrubland was ∼12 and ∼10 times of meadow steppe, respectively. Interactive mechanisms between biophysical factors and energy fluxes were ecosystem dependent. Abstract: Energy flux is a key component and driving factor in ecosystem processes and functions. Using 2015 datasets of eddy covariance, vegetation and meteorological measurements at four dominant ecosystems on the Mongolian Plateau, we analyzed the inter-site and seasonal variations and underlying biophysical controls on energy balance and partitioning in a meadow steppe (MDW), typical steppe (TPL), dry typical steppe (DRT) and shrubland (SHB). Vegetation dynamics dominated the energy partitioning. The growing season (May-Sept) net radiation ( R n ) was 20% less at SHB due to higher bare soil coverage area than that at MDW. High vegetation cover and soil water content resulted in the highest latent heat (LE) at MDW, while sparse vegetation showed the highest sensible heat ( H ) at DRT among the four vegetation types. The Bowen ratios ( β, H /LE) at TPL (1.68), DRT (1.44) and SHB (1.44) were an order of magnitude higher than that at MDW (0.14). At DRT and SHB, β had significantly negative feedback on canopy conductance ( p < 0.05) and significantly positive feedback on vapor pressure deficit (VPD) ( p < 0.05). We emphasized that the complex, interactive effects of vegetation types, ecosystem structures, and microclimate for the energy balance and partitioning.